Familial Clustering of Breast and Prostate Cancer and Risk of Postmenopausal Breast Cancer in the Women’s Health Initiative Study - Beebe-Dimmer, Jennifer L. (Cancer, 2015)
BACKGROUND: Evidence suggests that the risk of breast and prostate cancer is increased among those with a family history of the same disease and particularly among first-degree relatives. However, less is known about the relationship between breast and prostate cancer within families and particularly among minority populations. METHODS: Analyses of participants in the Women’s Health Initiative observational cohort who were free of breast cancer at the time of their baseline examination were conducted. Subjects were followed for breast cancer through August 31, 2009. A Cox proportional hazards regression modeling approach was used to estimate the risk of breast cancer associated with a family history of prostate cancer, breast cancer, and both among first-degree relatives. RESULTS: There were 78,171 eligible participants, and 3506 breast cancer cases were diagnosed during the study period. A family history of prostate cancer was associated with a modest increase in breast cancer risk after adjustments for confounders (adjusted hazard ratio [aHR], 1.14; 95% confidence interval [CI], 1.02-1.26). In a separate analysis examining the joint impact of both cancers, a family history of both breast and prostate cancer was associated with a 78% increase in breast cancer risk (aHR, 1.78; 95% CI, 1.45-2.19). Risk estimates associated with a family history of both breast and prostate cancer were higher among African American women (aHR, 2.34; 95% CI, 1.09-5.02) versus white women (aHR, 1.66; 95% CI, 1.33-2.08). CONCLUSIONS: These findings suggest that prostate cancer diagnosed among first-degree family members increases a woman’s risk of developing breast cancer. Future studies are needed to determine the relative contributions of genes and a shared environment to the risk for both cancers.